(untitled) (Journal of Advanced Research in Social Sciences, 2021)
By understanding the factors that impact how different people think, feel, or act, psychologists can gain insight that will allow them to predict how individuals are likely to behave in certain situations. One construct that has received recent attention in relation to personality is entitlement. A small number of studies have previously found relationships between specific personality traits and several narrow conceptualizations of entitlement. However, these studies have consistently studied entitlement from the perspective of a maladaptive trait that is closely tied to narcissism. Therefore, the current study examined the relationship between the Big Five Personality Traits and two different conceptualizations of psychological entitlement. A Pearson’s product-moment correlation was run to assess the relationship between each of the Big Five Personality Traits and entitlement as measured by the PES and the three factors of the EAQ (Active Entitlement, Passive Entitlement, and Revenge Entitlement). Extraversion was high for the PES and Active Entitlement but low for Revenge Entitlement, while Agreeableness was high for Passive Entitlement but low for Revenge Entitlement and the PES. Revenge Entitlement and PES show some overlap as maladaptive traits that are characterized by low Agreeableness. Revenge Entitlement emerged as the component of entitlement that was most closely associated with the Big Five Personality Traits, showing negative relationships will all of the personality traits except for Neuroticism.